2020
DOI: 10.3904/kjim.2019.218
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochlorothiazide use and the risk of skin cancer in patients with hypertensive disorder: a nationwide retrospective cohort study from Korea

Abstract: Background/Aims: Recent studies have shown a cumulative dose-dependent association between the use of hydrochlorothiazide (HCTZ) and skin cancer, including melanoma and non-melanoma skin cancer (NMSC) in Western Europe. However, whether this pattern is present in East Asia countries is unknown. The aim of this study was to examine the association between HCTZ use and the risk of skin cancer among a cohort of hypertensive patients in South Korea. Methods: This was a retrospective, population-based cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 37 publications
2
19
2
2
Order By: Relevance
“…Recently, a few studies were also conducted to clarify this association in Asia. From a nationwide cohort study conducted in South Korea, the protective effect of HCTZ has not observed the development of melanoma and non-melanoma skin cancer [ 27 ]. However, from another nationwide cohort study conducted in Taiwan, Pottegård et al have reached limited evidence of HCTZ use associated with an increased risk of skin cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few studies were also conducted to clarify this association in Asia. From a nationwide cohort study conducted in South Korea, the protective effect of HCTZ has not observed the development of melanoma and non-melanoma skin cancer [ 27 ]. However, from another nationwide cohort study conducted in Taiwan, Pottegård et al have reached limited evidence of HCTZ use associated with an increased risk of skin cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although two recent East Asian studies showed no significant association between HCTZ use and risk of NMSC, 11,12 one was a case-control study with a short follow-up period 11 and the other had potential selection bias because only patients with hypertension were included. 12 Thus, we performed a long-term retrospective cohort study of Korean participants using a nationwide sample cohort to investigate the risk of NMSC in relation to use of HCTZ and the effect of age on the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…We thank Drs. Pottegard and Morales for their thoughtful comments on our article entitled "Hydrochlorothiazide use and the risk of skin cancer in patients with hypertensive disorder: a nationwide retrospective cohort study from Korea" [1].…”
mentioning
confidence: 99%